Conceptual design of an autonomous single-container vessel - Hompes, Jouke Thomas; Sebastiaan Hendriks, Pieter Max; Tjalling Cuijpers, Jelle Paul; Frederik Wolterbeek, Ties Johannes; Sougé, Wouter Dick; Nishiki, Yoshinari; Garofano, Vittorio; Jovanova, Jovana (Frontiers in Future Transportation, 2024)
The growth of maritime shipping is leading to the creation of larger vessels.However, this expansion in size brings with it several challenges, including the development of maritime infrastructure, the potential for growth in third world countries, and the emission of greenhouse gases. At present, there is no way to transport a single container overseas with a minimal carbon footprint. This research examines the design of an autonomous ship that is capable of transporting a single standardized 40 ft. container overseas using mainly passive propulsion methods. Using advanced design tools, including CAD software and CFD simulations, as well as conducting a comprehensive analysis of relevant literature, the designs for a hull and sails were developed, and an overview of the potential active control systems required for autonomous operation was provided.The study also performed an initial analysis of strength, stability, and velocity to validate the design choices. The results of the study indicate that it is possible to design and manufacture a mainly passively propelled ship capable of transporting a 40 ft. standardized container overseas and rethink the logistics at scale.